Pattern-Based Assessment of the Association of Fetal Heart Variability With Fetal Development and Maternal Heart Rate Variability - Namareq Widatalla; Mohanad Alkhodari; Kunihiro Koide; Chihiro Yoshida; Yoshiyuki Kasahara; Masatoshi Saito; Yoshitaka Kimura; Ahsan Khandoker (IEEE Access)
Prenatal assessment of fetal development is primarily carried out by measuring fetal heart rate (HR) and HR variability (HRV). HRV has been used as an index for the autonomic nervous system (ANS) activity. Hence, fetal ANS (fANS) development has been assessed in previous literature by evaluating fetal HRV (fHRV) at different gestational ages (GAs). Previously, it was demonstrated that fHRV was affected by factors such as fetal behavioral states and maternal conditions. Therefore, reliable evaluation of fANS development based on fHRV depends on the appropriate assessment of fHRV. In this study, we develop an HRV parameter based on maternal and fetal HRV to assess fHRV. The parameter was calculated by using 5-minute segments of non-invasive maternal and fetal electrocardiogram (ECG) records (158 subjects (GA: 19 - 40 weeks)). The parameter was developed by first counting the number of R peaks per 2 seconds (nRpp2s) and then calculating the standard deviation (SD) of nRpp2s (snRpp2s). After that, the HRV parameter was obtained by calculating the difference between maternal and fetal snRpp2s (dmf). The dmf was used to divide data into three patterns to evaluate the association of fHRV with GA and maternal HRV (mHRV) per pattern. The results showed discrepancies in the degree of association of fHRV with GA, implying that fHRV is not always an indicator of fANS development. These differences are expected due to maternal-related influences, as maternal HRV (mHRV) shows a pattern-specific association with fetal HRV (fHRV), that is, the two are correlated in some patterns but not in others. In addition, a comparison analysis of fHRV among the three patterns revealed that the discrepancies concerning fHRV could also be related to fetal behavioral states. The findings of this study provide a novel approach to assessing fHRV and fetal development relative to mHRV.